'Stay away from home': The role of social networks for the adaptation process of Indonesian trainees in Japan - Andiline Thea Pranasari; Kurniawaty Iskandar (Universitas Negeri Yogyakarta, 2022)
This study aims to analyze the challenges faced by Indonesian trainees, especially the participants of Technical Intern Training Program (TITP), in the process of adapting to Japan's socio-cultural system. Furthermore, this study finds out how the role of social networks in the process of adapting the lives of the trainees. Social network theory and social capital will be used as a perspective to analyze the existing phenomena. Data collection process and analysis of findings will be carried out based on qualitative research methods. Primary data sources were taken by using in-depth interviews towards three Indonesian trainees, complemented by secondary data from related research and articles. The results of the study show that the challenges faced by Indonesian trainees include difficulties in adapting to work, limitation of Japanese language proficiency, lack of opportunities to practice prayers regularly, and difficulties to build social relationships. In dealing with these problems, trainees receive moral assistance and information about the way of life in Japan from the Indonesian networks. The adaptation process of Indonesian trainees in Japan is supported by social networks that are formed informally, and plays a role in maintaining the continuity of the migration pattern of Indonesian workers to Japan.